2009
DOI: 10.1016/j.ijpsycho.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Recognition without awareness in a patient with simultanagnosia

Abstract: We report a psychophysiological study of "recognition without awareness" in patient 2354, who had severe but circumscribed atrophy in the occipitoparietal region bilaterally (caused by visual-variant Alzheimer's disease, documented by structural and functional neuroimaging) and an accompanying Balint syndrome that prevented her from recognizing the emotional valence of many highly charged negative visual scenes (e.g., a burned body). Despite this lack of overt recognition, patient 2354 nonetheless generated la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…To our knowledge, only two case report studies (Denburg et al, 2009;Filoteo et al, 2002) have presented (2009) showed intact psychophysiological response between negative and neutral pictures. Also, their patient correctly identified the emotional valence of some images, which the authors interpreted as evidence for (relatively) spared perception without accurate identification.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, only two case report studies (Denburg et al, 2009;Filoteo et al, 2002) have presented (2009) showed intact psychophysiological response between negative and neutral pictures. Also, their patient correctly identified the emotional valence of some images, which the authors interpreted as evidence for (relatively) spared perception without accurate identification.…”
Section: Discussionmentioning
confidence: 96%
“…Initially, Filoteo, Friedrich, Rabbel, and Stricker (2002) reported the case of a patient who demonstrated augmented reaction times to incongruent items of a global-local recognition task, even though he failed to consciously identify global targets. More recently, Denburg, Jones, and Tranel (2009) used a psychophysiology index to examine a PCA patient, and found large amplitude of SCR to negative pictures, despite a lack of overt recognition. However, their experimental design did not include positive stimuli or, differences between objects and persons.…”
mentioning
confidence: 99%
“…14 Yovel and Paller (2004) noted that when participants experienced familiarity without identification, the magnitude of neural response (ERP) was reduced and occurred for a shorter duration, suggesting an absence of the type of context/biographical retrieval processing characteristic of identification (see also GrohBordin, Zimmer, & Ecker, 2006. 15 Denburg, Jones, and Tranel (2009), for example, measured an increase in SCR in a patient suffering from simultanagnosia. The increase corresponded to the presentation of negatively-charged stimuli (e.g.…”
Section: What Is It To Have a Sense Of Familiarity Without Identificamentioning
confidence: 99%
“…7 In 2009, researchers described an increased skin conductance response in a patient with PCA who was shown emotionally negative pictures. 10 In 2015, a report was presented on a woman with PCA who, despite showing decreased explicit visual recognition, retained some implicit awareness of image-associated valence and arousal. 9 We confirmed the relative preservation of FE recognition vs the recognition of FI among patients with PCA, which demonstrated that the difference between these 2 abilities was greater in patients with PCA than in patients with AD or patients with bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…8 Given the presumptive preservation of these pathways in PCA, despite the degeneration of cortical networks for visual processing, single case studies have suggested that recognition of emotionally salient stimuli may be preserved in PCA as in cortically blind patients. 9,10 Herein, we hypothesized that FE recognition would be relatively preserved in PCA (i.e., similar to other groups), compared to both facial identity (FI) recognition and other tests of visual function.…”
mentioning
confidence: 99%